2014
DOI: 10.9740/mhc.n198935
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and management of chronic pain in patients with depression and anxiety

Abstract: This article will review the role of the pharmacist in the management of chronic pain in patients with comorbid mood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
2
0
2
Order By: Relevance
“…The modulation of pain through these descending pathways is disrupted, and pain sensations are allowed to ascend to the brain [ 36 ]. It is reported that patients with chronic pain and comorbid mood disorders are often more difficult to treat, because of a difference in perception of pain, negative coping skills, the risk of drug abuse, and the negative influence of comorbidity on the outcomes of diagnosis [ 37 , 38 ]. That may explain why among patients with more severe depression at baseline, it was more difficult to get relieved from their orofacial pain in the follow-up after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The modulation of pain through these descending pathways is disrupted, and pain sensations are allowed to ascend to the brain [ 36 ]. It is reported that patients with chronic pain and comorbid mood disorders are often more difficult to treat, because of a difference in perception of pain, negative coping skills, the risk of drug abuse, and the negative influence of comorbidity on the outcomes of diagnosis [ 37 , 38 ]. That may explain why among patients with more severe depression at baseline, it was more difficult to get relieved from their orofacial pain in the follow-up after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Наиболее часто в практической деятельности невро-лога встречается паническое расстройство и генерализо-ванное тревожное расстройство [14,15].…”
Section: диагностика тревожных расстройствunclassified
“…Depression and anxiety add to pain because they may increase the likelihood of social isolation and kinesophobia, or the fear of movement due to pain ( 31 , 32 ). Additionally, the pathophysiology of depression and anxiety may use the same neurotransmitters that affect pain in the brain ( 33 ). Therefore, this relationship should be investigated further, especially in individuals with FM.…”
Section: Introductionmentioning
confidence: 99%